Experimental studies of liquid immersion cooling for 18650 lithium-ion battery under different discharging conditions. (June 2022) - Li, Yang; Zhou, Zhifu; Hu, Leiming; Bai, Minli; Gao, Linsong; Li, Yulong; Liu, Xuanyu; Li, Yubai; Song, Yongchen
Abstract: In this study, fluorinated liquid immersion cooling as a new cooling scheme has been tested and discussed for cooling the 18650 lithium-ion battery (LIB). SF33, with the boiling point of 33.4 °C, is chosen as the liquid for the immersion cooling. Comparison of the SF33 immersion cooling and forced air cooling (FAC) for the 18650 LIB under 2C, 4C and dynamic load conditions are made. It is found that the immersion cooling better cools the battery under all these conditions. Under 4C discharging, the maximum cell temperature rise is 14.06 °C for the FAC, while is 4.97 °C for the SF33 immersion cooling. As the temperature of SF33 basically governs the cell temperature, the SF33 temperature should not be too low. This study demonstrates that the LIB has non-negligible power losses under SF33 temperature of 10 °C and 15 °C, compared with the temperatures above 20 °C. Lastly, the two-phase boiling heat transfer mechanisms associated with immersion cooling are discussed with bubble dynamics analysis. It is found under a higher C rate, more aggressive boiling heat transfer is induced. The battery temperature is controlled to be below 34.5 °C even under 7C discharging condition.